Analyzing the Decline and Revival of Tamil Nadu Traditional Games (International Journal of Food and Nutritional Sciences, 2022)
This study explores the cultural and social significance of traditional games in Tamil Nadu, their historical roots, and the reasons for their decline in modern times. By surveying 500 respondents from rural and urban areas, it examines awareness levels, age-wise participation, and perceptions of the educational and developmental benefits of these games. The results show that traditional games are more familiar in rural areas, while urban respondents show lower awareness. Key reasons for their decline include the popularity of digital games, modern lifestyles, and the absence of these games in school curricula. Despite the challenges, the study highlights the potential of traditional games to promote physical fitness, strategic thinking, and cultural heritage. It advocates for initiatives to preserve and revive these games through education, cultural programs, and policy support to ensure their relevance for future generations.